Transcriptomic profiling of organoids derived from malignant effusions uncovers lncRNA MEG3 and target genes potentially involved in platinum resistance in serous ovarian carcinoma - Calanca, Naiade [UNESP]; Rainho, Claudia Aparecida [UNESP]; Maeda, Debora Kazumi [UNESP]; Côrtes, Luiza [UNESP]; Villacis, Rolando André Rios; Bizinelli, Daniela; Kuasne, Hellen; Aagaard, Mads Malik; Fokdal, Lars Ulrik; Steffensen, Karina Dahl; Jensen, Lars Henrik; Rogatto, Silvia Regina [UNESP] (Elsevier, 2025)
Serous ovarian carcinoma (SOC) is an aggressive disease, characterized by advanced-stage tumors that are often associated with relapse and poor outcomes. Although platinum-based chemotherapy is a cornerstone of the treatment, most of the relapsed tumors become resistant to these agents. We explored organoids derived from SOC malignant effusions to identify targets actionable by epigenetic drugs (epi-drugs) to enhance platinum response. Tumor-derived organoids (TDOs) were established using malignant effusions of SOC patients. Histological and transcriptomic (RNA-Seq) characterization (18 TDOs versus 7 normal ovarian samples) was performed, followed by cross-validation with external RNA-Seq datasets (337 SOC samples, 4 TDOs, and 180 normal tissues). Predicted interactions between long noncoding RNAs (lncRNAs) and epigenetic effectors were investigated. We selected the epi-drugs decitabine and tazemetostat, whose targets were overexpressed in SOC, to treat carboplatin-resistant SOC cell lines and TDOs. Subsequently, these models were challenged with carboplatin. Twelve lncRNAs and 168 protein-coding genes differentially expressed were involved in epigenetic regulation. Abnormal expression levels of lncRNA MEG3 and epigenetic effectors DNMT3B and EZH2 were confirmed in external datasets. Increased carboplatin sensitivity and MEG3 upregulation were observed after treating the cell lines and TDOs with epi-drugs. Altogether, our findings provide novel insights into using organoids derived from malignant effusions as preclinical models and hint at potential targets for overcoming platinum resistance in SOC.